2018
DOI: 10.2337/db17-0371
|View full text |Cite
|
Sign up to set email alerts
|

PDGF-BB Carried by Endothelial Cell–Derived Extracellular Vesicles Reduces Vascular Smooth Muscle Cell Apoptosis in Diabetes

Abstract: Endothelial cell-derived extracellular vesicles (CD31EVs) constitute a new entity for therapeutic/prognostic purposes. The roles of CD31EVs as mediators of vascular smooth muscle cell (VSMC) dysfunction in type 2 diabetes (T2D) are investigated herein. We demonstrated that, unlike serum-derived extracellular vesicles in individuals without diabetes, those in individuals with diabetes (D CD31EVs) boosted apoptosis resistance of VSMCs cultured in hyperglycemic condition. Biochemical analysis revealed that this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…However, in our experimental setting, VSMCs acted as recipients in the perivascular microenvironment to accept miR‐221‐3p containing EVs. In recent reports, VSMCs could internalize EVs derived from endothelial cells (49) or macrophages (14). However, the exact loading mechanism of miR‐221‐3p into EVs was not addressed in this study and remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our experimental setting, VSMCs acted as recipients in the perivascular microenvironment to accept miR‐221‐3p containing EVs. In recent reports, VSMCs could internalize EVs derived from endothelial cells (49) or macrophages (14). However, the exact loading mechanism of miR‐221‐3p into EVs was not addressed in this study and remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…IGF‐1, as a growth factor, has the ability to reduce the apoptosis of periodontal ligament fibroblasts through participation in several signalling pathways 25 . In addition, TGF‐β, VEGF, PDGF and bFGF also influence the inhibition of apoptosis 26–28 …”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, TGF-β, VEGF, PDGF and bFGF also influence the inhibition of apoptosis. [26][27][28] The showed that the viability of PDL cells is decreased after storage for 6, 24, 48 and 72 hours in sterile HBSS at 37°C. 30 Souza et al found that the storage time in HBSS has a negative influence on its ability to promote the proliferation of periodontal ligament fibroblasts, and it is suspected that HBSS storage may cause an alteration in the concentration of its components, making them insufficient to nourish the cells for more than 6 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of miRNAs have profound effects on cancer progression and human carcinogenesis (15). The expression of miR-296-5p has been shown to be significantly downregulated in lung cancer (3,16,17), breast cancer (18), diabetes (19)(20)(21) and other types of cancer and diseases (17,22,23). Therefore, exploring the function of miR-296-5p and the role of its possible target genes is essential to the understanding of the molecular mechanism of this miRNA in NSCLC.…”
Section: Introductionmentioning
confidence: 99%